Centrality of Religiosity and Dyadic Coping in Close Romantic Relationships: Actor Partner Interdependence Model - Wendołowska, Anna M. (Religions, 2021)
Some studies suggest that religious people cope better with stress. For married couples, if partners perceive their relationship as sacred, supportive dyadic coping mediates the association of sanctification with marital satisfaction and well-being. In the current study, applying the actor-partner interdependence model to 116 Polish couples (n = 232), aged between 21 and 64 (males: M = 37.8, SD = 11.8; females M = 37.1, SD = 12.0), we examined the link between centrality of religiosity and dyadic coping. Although general dyadic analyses indicate that centrality of religiosity and dyadic coping are unrelated concepts, at the subscales level, we could observe few significant relationships. The results show that Polish religious men rate their common dyadic coping low. Actor effects in women are moderated by the type of relationship (cohabitation and civil marriage vs. catholic marriage).